The Internet of People, Things and Services - Lituchy, Terri R.; Portillo, Carol (Routledge, 2018)
Online purchasing has increased dramatically over the past 10 years, and the pace is expected to continue to accelerate. The Internet is one of the biggest disruptive technologies in the history of purchasing, radically changing the way consumers purchase goods and services. No longer needing to visit a physical store location, consumers can purchase goods and services via a connected device such as a smart phone, computer or tablet and voice-controlled virtual assistants in homes, appliances and cars. These devices create a more convenient method of researching purchases and purchasing through the interconnectivity of devices termed the Internet of Things (IoT). The IoT is expected to continue to transform the interaction between consumers and e-commerce purchasing. This research investigated demographic antecedent variables of online repurchasing behavior to better understand consumer online repurchasing in the world of IoT. Results indicated no significance impact of the predictor variables (gender, user experience, level of income or level of education) on intent to repurchase online. Recommendations for future research include a larger sample study with wider geographic dispersion and collecting more data on Internet usage psychographic behavior, including product-specific repurchasing behaviors.
An Examination of Online Repurchasing Behavior in an IoT Environment
Keywords: IoT; Repurchasing; Campus Tijuana